Factors Affecting Environmental Management Accounting and Environmental Performance: An Empirical Assessment - Zandi, Gholamreza; Lee, Hoyoung (International Journal of Energy Economics and Policy, 2019)
In today's world, businesses have no apparent geographical boundaries for functioning, trading and delivering products and services. However, given the threats to environmental sustainability, modern businesses are restricted to adopt several environmental policies to operate in existing the present globalized ecosphere. Thus, the present study aims to examine the relationship between internal and external drivers of environmental management accounting. In doing so, the study seeks out the association of customer influence, regulatory pressure and firm's moral and social responsibility on environmental management systems in the Indonesian manufacturing industry. Moreover, the current study is also motivated to investigate the impact of EMA on a firm's environmental performance. The current study applied a partial least square structural equation modelling. The results of PLS-SEM confirm that all variables have a positive and significant impact on environmental performance. The results conclude that customer influence, regulatory pressure, and moral & social responsibility have a positive and significant contributor in enhancing environmental management accounting system. Moreover, the results further confirm that environmental management accounting system also plays a significant role in boosting the environmental performance in Indonesia. Therefore, the current study recommends SMEs to give more focus on enhancing the moral and social responsibility among its employees and also make a good control over the regulation and customer influence. Keywords: Customer influence, Moral & Social Responsibility, Environmental Performance, Indonesia. JEL Classifications: Q55, Q50 DOI: https://doi.org/10.32479/ijeep.8369